O adulto idoso aprendiz de língua adicional : perfil cognitivo e sócio-afetivo - Borba, Lívia Schleder de (2021)
Studies in the field of bilingualism have found evidence that the mastery of more than one language can result in cognitive benefits throughout life, but few studies have addressed the cognitive and socio-affective effects of additional language learning in old age. Taking into account that individual differences among additional language learners increase over the years, the present study sought to trace a cognitive and socio-affective profile of the older adult learner of additional languages using a learner profile questionnaire created from evidence in the literature. To achieve this goal, this work analyzes two studies: Study which is a systematic review aimed at bringing together works that associated cognitive and socio-affective aspects of the older adult with additional language learning, and Study 2, in which 18 additional language older learners responded to three instruments: a socioeconomic classification instrument, a linguistic profile questionnaire and an additional language learner profile questionnaire. The results of this analysis show that in Study 1 there is still no consensus in the literature about the cognitive benefits of additional language learning initiated in old age. It is recognized, however, that the older adult can benefit from the additional language learning process in the socio-affective dimension. Corroborating to this data, the profile of the older learner found in Study 2 showed that older students have high socioeconomic status and education, have English as an additional language of preference and have difficulties in developing study strategies that improve their vocabulary learning. In addition, they associate most of the difficulties they encounter as learners with the aging process. As such, the profile of older adults learning additional languages presented here brings theoretical and methodological contributions to geragogy, offers foundation for teaching and learning choices, and contributes to the creation of teaching material aimed at this population.